Методи дослідження фоніки поетичного тексту - Настенко, Ольга; Nastenko, Olga (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розкрито методи дослідження звукової організації поетичного тексту. На основі розгляду вчень представників формального та структурального напрямів окреслено етапи упровадження їхніх методологій у вивчення фоніки. Проаналізовано ключові підходи в становленні міждисциплінарних методів у формуванні аналізу функціонування звукових повторів у тексті. Testing methods of poetic language sound organization have been considered in the article. On the grounds of representatives’ formal and structural trends doctrine the stages of phonics methodology implementation have been designated. Key formation approaches of sound repetition text analysis have been analyzed. Application of related disciplines methods for profound study ofphonics as a separate branch of literary criticism have been made topical.It has been shown that the introduction of precise methods to literary criticism analysis of poetic text sound organization by means of modern technologies increases the investigation objectivity of author’sindividual style.
Phonics Testing Methods of Poetical Text
Keywords: фоніка; формальний метод; емпіричні дослідження; структуральний аналіз; структурально-семіотична методологія; математично статистичний метод; phonics; formal method; empirical investigation; structural analysis; structural-semiotic methodology; mathematically-statistical method